Visceral pain as a triggering factor for fibromyalgia symptoms in comorbid patients. Issue 10 (October 2017) - Costantini, Raffaele; Affaitati, Giannapia; Wesselmann, Ursula; Czakanski, Peter; Giamberardino, Maria Adele
Abstract : Abstract: Fibromyalgia syndrome (FMS) is a central sensitization syndrome; however, peripheral pain sources potentially exacerbate its symptoms of chronic diffuse musculoskeletal pain and hyperalgesia. This prospective study evaluated visceral pain as a possible triggering factor for FMS pain and hyperalgesia in comorbid patients. Women with (1) FMS + irritable bowel syndrome (IBS); (2) FMS + primary dysmenorrhea (Dys); (3) FMS + Dys secondary to endometriosis (Endo); (4) FMS + colon diverticulosis (Div) were compared with FMS-only women, for fibromyalgia pain (number and intensity of episodes and analgesic consumption) over comparable periods and for somatic hyperalgesia (electrical and pressure pain thresholds) in painful (tender points) and control areas (trapezius, deltoid, quadriceps muscles, and overlying subcutis and skin). In comorbid subgroups, FMS symptoms were also reassessed after treatment of the visceral condition or no treatment. All comorbid groups vs FMS-only had significantly higher FMS pain (number/intensity of episodes and analgesic consumption) and hyperalgesia in deep somatic tissues (subcutis and muscle) at all sites (0.05 < P < 0.0001). Visceral pain (number of IBS days, painful menstrual cycles, and abdominal pain episodes from diverticulitis) correlated directly with all parameters of FMS pain and inversely with muscle pain thresholds at all sites (0.03 < P < 0.0001). Fibromyalgia syndrome pain and hyperalgesia in all tissues and all sites significantly decreased in patients after visceral comorbidity treatment (dietary for 6 months [IBS], hormonal for 6 months [dysmenorrhea], laser [endometriosis], and surgery [diverticulosis]) (0.05 < P < 0.0001) vs no change in untreated patients. Visceral pain enhances FMS symptoms, probably augmenting the level of central sensitization typical of the syndrome. Systematic assessment and treatment of visceral pain comorbidities should be a part of FMS management strategy. Abstract : Supplemental Digital Content is Available in the Text.Comorbid visceral pain in patients with fibromyalgia involves increased musculoskeletal pain and diffuse somatic hyperalgesia, probably from enhanced central sensitization by the visceral noxious inputs.